A produção científica de teses e dissertações sobre a ditadura militar brasileira (1964 -1985): um estudo de caso no Programa de Pós-Graduação em História Social da Universidade de São Paulo - Olívia Andrade Coimbra (2021)
The Brazilian Military Dictatorship (1964 - 1985) was the longest period of authoritarianism experienced in the country after the Proclamation of the Republic. They were years marked by violence, disregard for the basic principles of human rights and censorship of information. After the redemocratization, it became urgent to understand this historical period. Thus, this dissertation aims to research the scientific production that has as its theme the Military Dictatorship, analyzing the theses and dissertations of the postgraduate course in in Social History of the University of São Paulo (PPGHS-USP). Problematization is guided by the following question: How do the political-legal mechanisms that seek memory, truth, justice, and reparation in the context of Brazilian Transitional Justice influence the characteristics of the scientific production of theses and dissertations on the theme Military Dictatorship in Brazil (1964-1985) over time? More specifically, the research sought: to recover theses and dissertations from PPGHS-USP that deal with the theme; to characterize them from the indicators, i.e.: a) occurrence of production, b) thematic occurrence, c) occurrences of bibliographic references, d) occurrence of producers (authors and advisors); to identify the chronology of political-legal mechanisms that seek memory, truth, justice and reparation between the years 2000 to 2019 and analyze the variations and frequencies of scientific production, using the chronology proposed as a reference. The methodological procedure adopted is the case study because it provides greater depth of analysis. For data collection, the documentary research technique is used. The methodology has qualitative logic, however, a combination of qualitative and quantitative techniques is used, to make the research more robust. Thus, data analysis occurs in two dimensions: through bibliometric analyses, used to describe the characteristics of the scientific production of PPGHS, and through content analysis, used to identify the chronology of political-legal mechanisms and understand and organize the content of theses and dissertations. The chronology analysis stage revealed that the period with the highest number of actions aimed at transitional justice is between 2002 and 2015. From the searches carried out in the Brazilian Digital Library of Theses and Dissertations, 83 theses and dissertations were recovered that deal with the theme military dictatorship, verifying the growth of production from 2007, with great concentration from 2014. The analysis of the occurrence of production pointed out that there was correspondence between the periods of higher productivity of theses and dissertations with periods of implementation and achievements of the organs related to the mechanisms of transitional justice, especially the National Truth Commission. In view of the analysis of the variables, it was contacted that the mechanisms of transitional justice are not determinant for the production of theses and dissertations, but they can influence it, as they offer new information sources, reveal obscured memories, reconstruct new versions of past facts, expand access to information and foster debate about the military dictatorship, focusing on the interest on the subject, on the elaboration of memories and in the construction of new knowledge in relation to this traumatic past.